Smart Working Orientation dan Customer Orientation; Implikasinya terhadap Kinerja Tenaga Penjualan Multi Level Marketing: Smart Working Orientation and Customer Orientation; Implications for Multi Level Marketing Sales Force Performance - Sari, Dewi Komala (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
It is important to create a reliable, smart, hard working and customer oriented distributor in a company engaged in the field of Multi Level Marketing in an attempt to develop a network of distributors to increase the sales volume. The problem faced by the company today is how to create human resources, particularly the distributors who can produce the optimal performance resulting in increasing sales volume as the company's goals can be achieved. The purpose of the study is to analyze the effect of smart working orientation and customer orientation to the variable of sales performance of PT. Tianshi Branch Surabaya. Here, by knowing the influence of these factors on sales performance, the researcher can determine how to maintain and improve the distributor's sales performance. The study uses primary data collected by distributing questionnaires to the distributor of PT. Tianshi Branch Surabaya. The analytic technique used is Structural Equation Modeling in order to determine the causality between analyzed variables. Based on the results of data processing, it can be concluded that the Orientation Working Smart factor does not have an impact to the sales performance factor, and the customer orientation factor has a positive effect on the sales performance factor of PT. Tianshi Branch Surabaya.